Pengembangan Media Pop-Up Book Berbasis Religius untuk Meningkatkan Literasi Sains pada Materi Tata Surya Kelas VI MI Salafiyah - Dia Nada Kriswahyuni; Nurhaningtyas Agustin (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study was motivated by the low level of students’ scientific literacy in science learning due to the limited use of innovative learning media. The study aimed to develop a religious-based pop-up book media on the solar system material for sixth-grade students at MI Salafiyah that is valid, practical, and effective in improving students’ scientific literacy. This research used the Research and Development (R&D) method with the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included material experts, media experts, teachers, and 38 sixth-grade students at MI Salafiyah. Data collection techniques used observation, questionnaires, documentation, and tests. The instruments used were material validation sheets, media validation sheets, learning implementation sheets, student response questionnaires, and pretest-posttest questions. Data analysis techniques used percentage analysis and N-Gain analysis. The results showed that the media obtained a material validation score of 100% and a media validation score of 85.7% with a very valid category. The practicality test showed a percentage of 100% with a very practical category. The effectiveness test showed an N-Gain score of 0.80 in the high category. Therefore, the religious-based pop-up book media is feasible and effective to improve students’ scientific literacy in science learning.